Ukiran Nusantara: Kriya Kulit dan Teknik Pyrography Meningkatkan Wawasan Budaya Siswa SMK Negeri 9 Surakarta - Arfiati Nurul Komariah; Novita Dwi Wulandari; Anastasia Irma Riani; Annisa Noer Cholizzhoh (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Community Service (PKM) entitled Archipelago Carving: Leather Craft and Pyrography Techniques to Increase Cultural Insight of Students of SMK Negeri 9 Surakarta. This community service activity is targeted at Vocational High School (SMK) students with a focus on Craft Design and Production (DPK) expertise in the fields of Batik-Textile Craft, Jewelry Metal Craft, and Rattan Wood Craft, precisely at SMK Negeri 9 Surakarta Jl. Tarumanegara I, Banyuanyar, Kec. Banjarsari, Surakarta City, Central Java. SMK Negeri 9 Surakarta does not have a leather specialist, despite the cultural significance of leather art. To address this, a community service initiative aims to introduce pyrography carving techniques applied to vegetable tanned leather to the students. This is expected to improve students' skills while fostering appreciation for local culture and creating innovative and valuable handicraft products amidst the declining interest in traditional arts among young people. So that the output of this PKM activity is the existence of leather craft products from students and collaboration opportunities between the author and SMK Negeri 9 Surakarta.